AB0946 S100A8 but Not S100A9 Level Is Related To The Extent of Erosive Bone Damage in Psoriatic Arthritis Patients. (15th July 2016) - Simon, D.; Nas, K.; Faustini, F.; Kleyer, A.; Haschka, J.; Englbrecht, M.; Hueber, A.J.; Kocijan, R.; Sticherling, M.; Schett, G.; Rech, J.
Abstract : Background: Psoriasis and psoriasis arthritis are associated with bone damage [1–3]. However, little is known about markers associated with structural bone damage in patients with psoriasis (PsO) and psoriasis arthritis (PsA). C-reactive protein is of limited use in PsO and PsA and therefore development of new markers is needed to identify patients with higher level structural bone damage. The calcium-binding proteins S100A8 and S100A9, which are predominantly produced by myeloid cells and elevated in certain forms of inflammatory diseases are interesting candidates. Objectives: To analyse whether S100A8 and S100A9 serum levels are related to structural bone damage in patients with PsO and PsA. Methods: Both PsO and PsA patients (according to the CASPAR criteria) were analysed. Demographic and disease-specific variables were recorded. Bone architecture was assessed by high-resolution peripheral quantitative computed tomography (HR-pQCT, XtremeCT, Scanco, Switzerland) of the metacarpal heads 2 and 3. Number and size of bone erosions were quantified as described previously [1]. Levels of S100A8 and S100A9 were measured by enzyme-linked immunosorbent test. Serum markers were correlated to the extent (volume) of bone erosions, respectively using Spearmans correlation. Results: 94 patients were included into this combined imaging and serum analysis, 42 of them had PsO (18 female, mean age 48.4±12.8 years) and 52 had PsA (29 female, age 48.3±14.8 years). Duration of skin disease was 14.7±16.1 years in PsO and 13.3±13.6 years in PsA. Duration of joint disease in PsA was 4.6±5.9 years. Mean time between blood collection and HR-pQCT measurement was 0.3±1.7 days (maximum 10 days). Mean±SD S100A8 level was 11.8±15.3 ng/ml in PsO patients and 12.8±13.8 ng/ml in PsA, while mean ±SD S100A9 level was 66.8±51.1 ng/ml in PsO and 75.9±58.3 ng/ml in PsA. Mean±SD erosion volume was 0.7±1.8 mm 3 in PsO patients and as high as 2.2±3.6 mm 3 in PsA. Serum levels of S100A8 were significantly correlated to erosion volumes ( ρ =0.327 (p=0.019)) in PsA but not in PSO. No significant correlation for S100A9 was found. Conclusions: S100A8 but not S100A9 level is significantly correlated to the extent of structural bone damage in patients with PsA. Hence, S100A8 may emerge as an interesting biomarker for determining the severity of psoriatic disease, especially the extent of structural bone damage. References: Simon D, et al. Ann Rheum Dis 2014;73:464–5. Finzel S, et al. Ann Rheum Dis. 2011;70:122–7. Kocijan R, et al. J Bone Miner Res. 2015;30:1775–83. Disclosure of Interest: None declared